PENGARUH METODE PEMBELAJARAN ROLE PLAYING TERHADAP HASIL BELAJAR IPS SISWA - Febri Larasati; Ali Mashari; Nureva Nureva (STKIP Al Islam Tunas Bangsa Bandar Lampung, 2020)
The purpose of this study was to determine the effect of the role-playing learning model on student learning outcomes in Social Sciences (IPS) subjects in Class V SD Negeri 3 Siderejo. This research is a quasi-experimental study conducted in class V SD Negeri 3 Siderejo. Based on research conducted in class V SD Negeri shows that there is a significant influence from the application of the Role Playing learning model on student learning outcomes in Social Sciences (IPS) subjects. This can be seen based on the average of student learning outcomes using the role-playing learning model is 85.26. While the average student learning outcomes using conventional learning models is 73.18. Based on the results of the t-test which obtained 6.246 > 2.05228. Thus it is hoped that SD/MI teachers will apply the role-playing learning method in social studies learning to improve student learning outcomes.